OPPORTUNITIES FOR THE DEVELOPMENT OF SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP BASED ON GLOBAL EXPERIENCE - Akhmedova Nilufar Shukhratovna (Web of Journals Publishing, 2025)
This article analyzes the global experience of developing small business and private entrepreneurship and examines the possibilities of applying this experience in the context of Uzbekistan. The study explores institutional, financial, and organizational mechanisms for supporting small businesses in different countries. Particular attention is paid to improving the business environment, enhancing competitiveness, and fostering innovation. Based on the findings, practical recommendations for the development of small business and private entrepreneurship are proposed.
Keywords: Small business, private entrepreneurship, global experience, support mechanisms, business environment, innovation, development.